PENGARUH MODEL PEMBELAJARAN DAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM SEKOLAH DASAR KOTA DEPOK - Fazriyah, Nurul (Jurnal Pendidikan Dasar, 2015)
This study aims to determine the effect of integrated learning model and ability to think critically about the science learning outcomes. The study was conducted in SDN Kemiri Muka 1 Depok in class V in the academic year 2014/2015 using cluster random sampling was done to 80 students. Retrieval of data obtained through the test and analyzed using Analysis of Variance (ANOVA) two-lane design with treatment by level 2 x 2. The results showed that: (1) Natural Sciences learning outcomes of students who are given integrated learning model thematic integrative models higher than in groups of students who are given learning model fragmented, (2) there is an interaction effect between the ability to think critically about the science subjects by learning model thematic integrative learning outcomes Natural Sciences, (3) for students who have the ability to think critically high, the result of learning science students given thematic integrative teaching model is higher than the fragmented learning model and (4) for students who have the ability to think critically low yield higher learning science using fragmented models. The conclusion showed that the thematic integrative learning model with critical thinking skills can improve student science learning outcomes . Keywords:Model Of Integrated Learning, Critical Thinking Skills, Science Learning Outcomes Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran terpadu dan kemampuan berpikir kritis terhadap hasil belajar IPA. Penelitian dilakukan di SDN Kemiri Muka 1 Depok pada kelas V tahun pelajaran 2014/2015 menggunakan cluster random sampling yang dilakukan kepada 80 siswa. Pengambilan data diperoleh melalui tes dan dianalisis menggunakan Analisis Varians (ANAVA) dua jalur dengan desain treatment by level 2 x 2. Hasil penelitian menunjukkan bahwa: (1) hasil belajar IPA siswa yang diberikan model pembelajaran terpadu model tematik integratif lebih tinggi dari pada kelompok siswa yang diberikan model pembelajaran fragmented, (2) terdapat pengaruh interaksi antara kemampuan berpikir kritis terhadap mata pelajaran IPA dengan model pembelajaran tematik integratif terhadap hasil belajar IPA, (3) bagi siswa yang memiliki kemampuan berpikir kritis tinggi, hasil belajar IPA siswa yang diberikan model pembelajaran tematik integratif lebih tinggi dari pada model pembelajaran fragmented dan (4) bagi siswa yang memiliki kemampuan berpikir kritis rendah hasil belajar IPA lebih tinggi menggunakan model fragmented. Kesimpulan menunjukkan bahwa model pembelajaran tematik integratif dengan kemampuan berpikir kritis mampu meningkatkan hasil belajar IPA siswa. Kata kunci :Model Pembelajaran Terpadu, Kemampuan Berpikir Kritis, Hasil Belajar IPA.